Maternal Perception of Decreased Fetal Movement in One Twin: A Clue Leading to the Early Detection of Absent Variability due to Acute Twin-to-Twin Transfusion Syndrome - Hirotada Suzuki; Tomoyuki Kuwata; Akihide Ohkuchi; Yukari Yada; Shigeki Matsubara; Mitsuaki Suzuki (Case Reports in Obstetrics and Gynecology)
Decreased fetal movement (DFM) perceived by pregnant women sometimes indicates imminent fetal jeopardy. It is unknown whether this also holds true for twin pregnancy. A 27-year-old primiparous woman with monochorionic diamniotic (MD) pregnancy had a slight difference of amniotic fluid volume at 312/7 weeks of gestation. DFM only in one twin at 314/7 weeks of gestation prompted her to receive urgent consultation. Since cardiotocogram indicated absent variability of one twin, we performed Cesarean section. Male infants weighing 2060 g and 1578 g were delivered; hemoglobin was 20.7 versus 10.8 g/dL, respectively; cardiothoracic ratio was 70% versus 44%, respectively, indicating acute twin-to-twin transfusion syndrome (TTTS). The recipient infant had heart failure, which was still observed at 1 month postpartum. In conclusion, maternal perception of DFM indicated imminent fetal death or jeopardy caused by acute TTTS, suggesting that education regarding DFM for women with twin pregnancy may be clinically important.